Training and Mentoring In The Development Of Reading Literacy Assessment Questions For Junior High School Teachers In Ogan Komering Ilir: Pelatihan dan Pendampingan Pengembangan Soal-Soal Asesmen Literasi Membaca Bagi Guru-Guru Smp di Ogan Komering Ilir - Nurhayati, Nurhayati Nurhayati; Sholikhah, Hani Atus Sholikhah; Sucini, Emelia Sucini; Nuzula, Khalidatun Nuzula; Pratama, Nanda Elta Wira Pratama; Rahmah, Silvia Fardatul Rahmah (Universitas Lancang Kuning, 2024)
This dedication aims to enhance teachers' knowledge and skills in designing frameworks and developing ALM (Higher Order Thinking Skills) based questions. The method utilized involves training and mentoring. Training encompasses delivering content and simulating question design. The mentoring process involves question designing, reviewing, revising, validating, testing, assessing validity and reliability, and analyzing item questions. The outcomes of this endeavor indicate the following findings: The pre-test and post-test display a significant change. The average score for the pre-test was 60.33, whereas the average score for the post-test was 80.67, resulting in a difference of 20.34. The mean score for the question validation stands at 69.67 out of a total score of 76, or 91.67%. The average score for language validation is 67 out of a total score of 80, or 83.75%. This illustrates that the developed questions are deemed appropriate both in terms of question construction and language aspects. Validity and reliability tests demonstrate that the developed question items possess varying degrees of validity, reliability, difficulty levels, and discriminative power.